If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 5x + 6 Reorder the terms: 16 = 6 + 5x Solving 16 = 6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 16 + -5x = 6 + 5x + -5x Combine like terms: 5x + -5x = 0 16 + -5x = 6 + 0 16 + -5x = 6 Add '-16' to each side of the equation. 16 + -16 + -5x = 6 + -16 Combine like terms: 16 + -16 = 0 0 + -5x = 6 + -16 -5x = 6 + -16 Combine like terms: 6 + -16 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| 4y-(y-4)=-20 | | 3z-7=11 | | 25x+4=79 | | x+7=2x-5 | | 2x+11=46-3x | | 2x-1= | | 2n+14= | | 4x+3(2x+4)=132 | | -5y+3=8 | | 5x-3=-28 | | 4y-8+6y=12 | | 2r+9=-17 | | 9m+14=12m | | 3x-1=12x-55 | | (x-1)=-4x+29 | | 3x+36=10x-41 | | -2*2+((-1)3-3)2= | | 7.083333333=x^2-3x+6.75 | | 7.5(x-4)=-0.5x+34 | | x^2-(m+3)x+11=0 | | 14-4(3x+1)-8+2x-2= | | 8*14*11= | | 6x+59=12x+11 | | 3x^2-9x+20.25=21.25 | | q+14=8q+56 | | (2x+3)(x-1)=18 | | q+14=8q+8*7 | | x+12+8x=30 | | 7n+39=11n-13 | | u+4=4u-8 | | (2x+3)(x+1)=18 | | c+2c-5-5c=7 |